Inner-city ritual centre: reflect + facilitate culture - Mavunga, Tatenda (My University, 2009)
The built environment is a product of man’s rationales and understandings of space. It is on the basis of these understandings that man builds, to facilitate his ways of life. These “understandings”, are the discourses that each individual is born into and the “ways of life” are the cultural practices resulting from these discourses. Architecture being a product of cultural discourse is intended to facilitate cultural practices. Post 1994 South Africa, has inherited a Johannesburg inner-city built environment, which is predominantly a product of apartheid and colonial discourse. During this era, black people were marginalised and excluded from the inner city, both physically and through architectural representation. The inner city was built in accordance with western (white) discourse to facilitate western cultural practices. Today the inner city is predominantly inhabited by black people, who were excluded and marginalised in its conception. Post colonial theorists assert that, while black people have embraced “modernity” and “western urbanity”, it has not resulted in a complete acceptance or appropriation of western cultural practices and discourses. Due a process termed “post colonial hybridity” these people merge the two seemingly irreconcilable cultural discourses and practices to form new cultural hybrids. The consequence of hybridity in the inner-city is; while the appropriated western cultural practices and discourses are inherently reflected and catered for, the retained aspects of black cultural practice and discourse remain marginalised. The built environment, which is meant to facilitate and reflect, negates and marginalises aspects of black discourses and cultural practices. “To be truly expressive, a building should grow out of its natural, social, and civilization context. It should reflect not only the personal values, needs and interests of its dwellers but also its relation to its natural and architectural site. Thus the formal organization of a building cannot be imposed on a people from the outside; it should originate from the context of human life in the given region. In this origination the process of spatial articulation results from a thought- full grasp of the dynamic interaction between the material elements of the architectural work and the human vision which guides this activity.” (Mitias 1994:103) In order to make a contribution to the creation of a more inclusive built environment this paper proposes the development of a hybrid building prototype that would facilitate and reflect the hybrid cultural practices and discourses of the city’s black inhabitants. The building prototype named the “Inner City Ritual Centre” aims to facilitate some of the marginalised practices of black people living in the city and to reflect some of the excluded spatial understandings of black people. The paper proposes a method of practice that utilises postcolonial hybridity, to include excluded and marginalised practices and discourses into the architectural representation of the city. This paper uncovers and highlights a few of these discourses and practices and demonstrates how the use of postcolonial hybridity in architecture would result in a more inclusive built environment.
Keywords: Blacks; Cultural practices; City planning; Johannesburg